Effect of long term agricultural management practices on enzyme activities in coastal alluvial soils of Pondicherry - M., SUDHAKARAN; D., RAMAMOORTHY; V., SAVITHA; M., KOKILA; A., RAVANACHANDAR (Journal of Soil and Water Conservation, 2021)
The objectives of study were to assess the effects of long-term management practices on soil nutrients and enzyme activities in coastal alluvial soils of Pondicherry, India. Long term organic (ORG), sustainable (SUS) and conventional (CON) farming soils were sampled. Organic farming soils had significantly higher amounts total nitrogen, phosphorus and potassium. In addition, plant available nutrients such as ammonium, extractable phosphorus, exchangeable potassium and organic carbon, concentrations were significantly higher in organic agricultural soils. Î²-glucosidase, cellulase, invertase, xylanase, Lasparaginase L- glutaminase, acid phosphatase and alkaline phosphatase enzyme activities were significantly higher in organic management system soils. However, amidase and arylsulphatase activities were not significantly influenced by agricultural management practices. Over all our results indicated that soil enzyme activities were strongly affected by agricultural management practices. Organic farming system had improved the plant available nutrients and enzyme activities that is contributed to enhance the soil health in coastal alluvium.